Surgical Team Stability and Risk of Sharps-Related Blood and Body Fluid Exposures During Surgical Procedures. (9th February 2016) - Myers, Douglas J.; Lipscomb, Hester J.; Epling, Carol; Hunt, Debra; Richardson, William; Smith-Lovin, Lynn; Dement, John M.
Abstract : OBJECTIVE: To explore whether surgical teams with greater stability among their members (ie, members have worked together more in the past) experience lower rates of sharps-related percutaneous blood and body fluid exposures (BBFE) during surgical procedures. DESIGN: A 10-year retrospective cohort study. SETTING: A single large academic teaching hospital. PARTICIPANTS: Surgical teams participating in surgical procedures (n=333, 073) performed during 2001–2010 and 2, 113 reported percutaneous BBFE were analyzed. METHODS: A social network measure (referred to as the team stability index) was used to quantify the extent to which surgical team members worked together in the previous 6 months. Poisson regression was used to examine the effect of team stability on the risk of BBFE while controlling for procedure characteristics and accounting for procedure duration. Separate regression models were generated for percutaneous BBFE involving suture needles and those involving other surgical devices. RESULTS: The team stability index was associated with the risk of percutaneous BBFE (adjusted rate ratio, 0.93 [95% CI, 0.88–0.97]). However, the association was stronger for percutaneous BBFE involving devices other than suture needles (adjusted rate ratio, 0.92 [95% CI, 0.85–0.99]) than for exposures involving suture needles (0.96 [0.88–1.04]). CONCLUSIONS: Greater team stability may reduce the risk of percutaneous BBFE during surgical procedures, particularly for exposures involving devices other than suture needles. Additional research should be conducted on the basis of primary data gathered specifically to measure qualities of relationships among surgical team personnel. Infect Control Hosp Epidemiol 2016;37:512–518